2010
DOI: 10.1177/1947601910368059
|View full text |Cite
|
Sign up to set email alerts
|

MUC1-C Oncoprotein Interacts Directly with ATM and Promotes the DNA Damage Response to Ionizing Radiation

Abstract: The ataxia-telangiectasia mutated (ATM) kinase is activated in the cellular response to ionizing radiation (IR) and is of importance to the repair of DNA double strand breaks (DSBs). The MUC1 oncoprotein is aberrantly overexpressed in human breast carcinomas. The present work demonstrates that the MUC1 C-terminal subunit (MUC1-C) constitutively interacts with ATM in human breast cancer cells. We show that the MUC1-C cytoplasmic domain binds directly to ATM HEAT repeats. Our results also demonstrate that the MU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…4 As found in the ATM-deficient mice, the size of the hematopoietic cell compartment was restored in the FoxOdeficient mice by treatment with NAC. 4,27 MUC1-C participates in stress-induced activation of ATM 29 and FoxO3a 19 and, thus, inhibition of MUC1-C in AML cells could also increase ROS and block self-renewal by affecting these pathways.…”
Section: Muc1-c Confers Aml Cell Survival By a Ros-dependent Mechanismmentioning
confidence: 99%
“…4 As found in the ATM-deficient mice, the size of the hematopoietic cell compartment was restored in the FoxOdeficient mice by treatment with NAC. 4,27 MUC1-C participates in stress-induced activation of ATM 29 and FoxO3a 19 and, thus, inhibition of MUC1-C in AML cells could also increase ROS and block self-renewal by affecting these pathways.…”
Section: Muc1-c Confers Aml Cell Survival By a Ros-dependent Mechanismmentioning
confidence: 99%
“…These functions allow MUC1 to facilitate tumor cell growth, invasion, motility, and cell survival under harsh conditions. Furthermore, MUC1 mediates DNA damage response by interacting with ataxia telangiectasia mutated (ATM) in breast cancer cells (16). MUC1 also interacts with c-Abl and prevents its nuclear targeting to block DNA damage-induced apoptosis (17).…”
Section: Introductionmentioning
confidence: 99%
“…We focused our study on 24 radiation responsive ERP29 ERP29 candidate genes because these genes were previously documented to be connected with functions intimately linked to cancer (Table 2). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Among the 24 genes, observations from previous studies noted post CT changes within 1 hour after radiation in 11 genes with 4 of them (ATM, ERP29, TP53, CDKN2A) showing post CT changes from very low radiation doses, as low as 0.1 Gy. Owing to their higher radiosensitivity, children are expected to react more sensitively than adults to the CT-induced radiation insult, and therefore, we included all 24 genes in our study, although some observations were reported longer than 1 hr post CT or after IR doses higher than those used in our study.…”
Section: Discussionmentioning
confidence: 99%